Regional Variation in the Carbon Dioxide Emission Efficiency of Construction Industry in China: Based on the Three-Stage DEA Model - Weizhong Zhou; Wenhua Yu (Discrete Dynamics in Nature and Society)
China’s construction industry emits a huge amount of carbon dioxide with the extensive and rapid development, and the carbon dioxide emissions from construction sector have become a social problem. This article evaluates the carbon dioxide emission from China’s regional construction industry by the three-stage DEA method. The research results indicate that the environmental factors and random error seriously affect the carbon dioxide emission efficiency of construction industry. Eliminated the above factors, the mean of the carbon dioxide emission efficiency has the tendency of rising firstly and then decreasing, which increased from 0.67 in 2010 to 0.76 in 2014 and then decreased to 0.66 in 2019 in the third stage. On the whole, China’s regional construction industry has the low carbon dioxide emission efficiency. In the regions, the Eastern region has the highest technology efficiency value among the three regions, followed by the Middle region and the West region. Therefore, the key method to increase the carbon emission efficiency of construction industry is to improve the management efficiency and change the growth mode.